Tahapan dalam Produksi Komposisi Iringan Tari Satya Gora Dharma - Komang Wahyu Dinata; I Pt. Lukita Wiweka Nugraha Putra (Journal of Music Science, Technology, and Industry, 2023)
Purpose: This paper discusses the series of stages of production of Satya Gora Dharma Dance Accompaniment composition, where this work is a karawitan composition work that the author made in 2021. Method: This work is produced by the author using Digital Audio Workstation technology, with a series of stages starting from the beginning until this work is completed. Digital Audio Workstation is a digital-based technology that is often used by musicians, arrangers, composers and other work sectors related to data processing in the form of audio recordings. Satya Gora Dharma dance is the great dance of Satya Dharma Singaraja College of Economics (STIE) initiated by Dr. A.A.A.N Tini Rusmini Gorda, Dr. A.A.N Oka Suryadinatha Gorda, Dr. A.A.N Eddy Supriyadinata Gorda, Dr. A.A.A.N Sri Rahayu Gorda. Satya Gora Dharma dance accompaniment compositions are produced with 3 software, namely Cubase Pro 10.5, WaveLab Pro 10, and Virtual Studio Technology (VST) from Native Instrument Kontakt 6. Result and Discussion: The discussion in this paper will focus on how this composition work is produced starting from the stage of taking audio sampling from the gamelan instruments used, making VST, composing arrangement, mixing, balancing, to the final stage in the production process, namely the mastering stage. The data analysis technique used in this paper is qualitative descriptive analysis. The qualitative descriptive analysis technique is carried out by analyzing the data that has been obtained through qualitative descriptive analysis. Then at the end a conclusion is drawn and accompanied by the necessary advice